Progress and Prospects in the Treatment of Lacrimal Gland Dysfunction Diseases: From Traditional Treatment Methods to Stem Cell and Organoid Therapies - Xiaona Chen; Shixu Li; Yongxin Zhang; Lin Ye (Stem Cells International)
Lacrimal gland (LG) dysfunction diseases are a type of disorder caused by various etiologies that damage the LG tissue, reducing lacrimal fluid secretion, triggering aqueous-deficient dry eye (ADDE), and causing a series of complications like keratoconjunctivitis sicca, potentially threatening vision. Our review summarizes the limitations and new progress of traditional treatment methods for LG dysfunction diseases. Meanwhile, we conduct in-depth analyses closely centered on the two emerging and cutting-edge research hotspots, namely stem cell therapy and organoid therapy. We have comprehensively evaluated the current research status regarding various stem cells, their derived extracellular vesicles, and LG organoid transplantation, further discussed the existing deficiencies, and subsequently put forward the prospective directions for future research. These include developing ophthalmic preparations of extracellular vesicles and LG stem cells or searching more efficient drug delivery systems, as well as culturing LG organoids that are highly similar to human lacrimal glands (LGs) in both function and microstructure through magnetic three-dimensional (3D) bioprinting technology and microfluidic 3D bioprinting technology.